2019
DOI: 10.1111/jgs.15722
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication Prescriptions for Older Adults with Painful Conditions and Association with Return Emergency Department Visits

Abstract: Objectives To describe the frequency and risk of return visit to the emergency department (ED) by older adults after prescription of any of four potentially inappropriate medication (PIM) classes included in the 2015 Beers Criteria commonly used for the relief of acute pain in the ED. Design Retrospective cohort study. Setting Large urban academic ED from January 1, 2013, to December 31, 2015. Participants Patients age 65 and older discharged from the ED with an initial pain score of 1 or higher (11 822 visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to determine characteristics of PIM use and assess the occurrence of subsequent falls in elderly patients with DRF. Chukwulebe et al [19] and Akkawi et al [20] reported PIM use rates of 28.7% and 28.5%, respectively, among elderly individuals. On the other hand, Huang et al [21] reported that 67.3% of patients receiving home care use PIMs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to determine characteristics of PIM use and assess the occurrence of subsequent falls in elderly patients with DRF. Chukwulebe et al [19] and Akkawi et al [20] reported PIM use rates of 28.7% and 28.5%, respectively, among elderly individuals. On the other hand, Huang et al [21] reported that 67.3% of patients receiving home care use PIMs.…”
Section: Discussionmentioning
confidence: 98%
“…Chukwulebe et al [ 19 ] and Akkawi et al [ 20 ] reported PIM use rates of 28.7% and 28.5%, respectively, among elderly individuals. On the other hand, Huang et al [ 21 ] reported that 67.3% of patients receiving home care use PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…Pain management is the central part of the treatment both before and after musculoskeletal interventions [ 39 – 41 ]. That these medications may be prescribed inappropriately is well documented in the literature [ 42 45 ] and their prescription is recommended only after a sound consideration of the benefits and risks. Nonetheless, this finding is intended to raise awareness particularly among healthcare providers outside the hospital setting regarding the prescribing practices of anti-inflammatory and anti-rheumatic PIMs.…”
Section: Discussionmentioning
confidence: 99%
“…PIMs are defined as medications that should be avoided due to their risk outweighing their benefit, 12,13 and explicitly listed in the Beers Criteria which is a commonly used tool to evaluate prescribing of PIMs in older adults. 14 While prescribing of PIMs in older adults has been shown to be prevalent 10,12,[15][16][17][18] and has a direct association with an increased ADE incidences, 5,6,15,18 the impact of PIMs on ADE rates and consequential clinical outcomes in older adults are largely unknown at a national level.…”
Section: Introductionmentioning
confidence: 99%